Technologies for Ultrapure Water Production in Semiconductor Industry - Duc Viet, Nguyen; Thi Thu Huong, Hoang; Ngoc Thuy, Vu (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 2S, 2025)
The semiconductor industry has become one of the most critical pillars of the global economy, with projected revenues expected to exceed USD one trillion by 2030. A key but often underappreciated resource underpinning semiconductor manufacturing is ultrapure water (UPW), which is indispensable for wafer cleaning, photolithography, chemical vapor deposition, and other precision processes. This review provides an overview of emerging technologies in UPW production for semiconductor manufacturing that have long been employed and remain foundational to UPW systems. We also emphasize the importance of integrated solutions with advanced oxidation processes, solar-driven energy system, and artificial intelligence. Together, these synergies create pathways toward greener, more resilient, and economically viable UPW production. These strategies are expected to ensure superior water purity, operational efficiency, and environmental sustainability, thereby supporting the long-term growth and competitiveness of the semiconductor sector.